"Bringing back hope": how faith-based responses to HIV and AIDS differ from secular responses. Issue 2 (3rd April 2018) - Simpson, Deborah
Abstract : This article investigates an assertion by faith-based organisations (FBO) that spirituality is the defining feature of their HIV and AIDS interventions. It is based on interviews with 24 people working on the issue of HIV and AIDS in churches or church organisations in Johannesburg, Rustenburg, Pretoria, Durban, Pietermaritzburg, and Cape Town. The article critically assesses the perceived difference between faith-based responses to HIV and AIDS and secular responses, including government programmes, in relation to the research literature on spirituality. After introducing the article, the argument begins with an exploration of the literature on churches and HIV and AIDS, outlining a gap which the article seeks to fill. The article then discusses the methods used for interviewing and analysing interview material. This is followed by religious leaders' own comments on how faith-based responses to HIV and AIDS differ from secular responses. The article concludes with a discussion which brings the literature to bear on the interview excerpts and then outlines the implications of decreased international funding for the HIV and AIDS programmes operated by the Anglican and Catholic churches, for example, a likely reduction in the accompaniment and monitoring of those who are HIV-positive.